Markerless Tracking Based on User Defined Targets to Enhance User Experience in Android-Based Furniture Visualization Applications - Indra Wijaya; Supriyanto Supriyanto (Jurnal Teknologi Informasi dan Multimedia, 2025)
Furniture is essential for daily activities and enhances the aesthetic appeal of various environments, including residences, commercial establishments, and cafes. Traditionally, furniture retailers display their products through catalogs or brochures. However, such media often fail to provide a comprehensive view of the furniture, hindering prospective buyers from evaluating items from all angles or determining their suitability for a specific room. This study proposes developing an Android application for interior layout design. It addresses these challenges by employing Augmented Reality technology in conjunction with a Markerless User Defined Target technique. The utilization of markerless user-defined targets is particularly advantageous, as it eliminates the requirement for predefined physical markers. This simplifies the process for the user and offers greater flexibility compared to conventional marker-based approaches, representing a key novelty of this work. The resultant software features a product catalog and comprehensive product information. It also allows users to view 3D augmented reality items, as well as scale, rotate, and manipulate these objects within their environment. Two individuals verified the system's operation through functional testing employing the Blackbox methodology. Usability testing, using the System Usability Scale, yielded above-average ratings, categorizing the software as "acceptable." Further examinations of viewing distance and angle indicated that camera quality influences augmented reality range, with AR objects remaining visible at angles ranging from 90° to 40°. These evaluations indicate that the Markerless User Defined Target method is effective and suitable for AR-based interior furniture layout planning.